Bad girls - Wilson, Jacqueline; Sharratt, Nick (New York : Dell Yearling, 2002)
Ten-year-old Mandy must endure torment from three nasty bullies in school, but she finds solace in a new friendship with an older girl.
"First published in Great Britain by Doubleday ... 1996"--T.p. verso.
Book Links (A.L.A.).
Publisher's Weekly.
School Library Journal.
5.1.
5.1
Keywords: Bullies -- Fiction; Friendship -- Fiction; Schools -- Fiction; Bullies -- Fiction; Friendship -- Fiction; School stories; England -- Fiction; England -- Fiction